A simple excited-state intramolecular proton transfer probe based on a new strategy of thiol–azide reaction for the selective sensing of cysteine and glutathione. Issue 4 (13th November 2015) - Zhang, Dan; Yang, Zihao; Li, Hongjuan; Pei, Zhichao; Sun, Shiguo; Xu, Yongqian
Abstract : A simple azido-substituted fluorescent sensorAHBO based on the mechanism of nucleophilic substitution–rearrangement reactions showed selective turn-on response to cysteine (Cys) and glutathione (GSH). Abstract : A simple azido-substituted fluorescent sensorAHBO showing a selective turn-on response to cysteine (Cys) and glutathione (GSH) over homocysteine (Hcy), sulfide and other amino acids has been constructed, which is based on the mechanism of selective nucleophilic substitution–rearrangement reactions.